Tinjauan Yuridis Pengenaan Sanksi Kurungan Pengganti Denda bagi Pelaku IUU Fishing di ZEE Indonesia - Riandy, Ervin; Pustika, Anna Anindita Nur; Christmas, Sandy Kurnia; Serera, Aulia Yuti (Shar-E : Jurnal Kajian Ekonomi Hukum Syariah, 2026)
The problem regarding the interpretation of the meaning of imprisonment and corporal punishment as stated in Article 73 paragraph (3) of UNCLOS 1982 has caused differences in judges' decisions against perpetrators of IUU Fishing in the Indonesian Exclusive Economic Zone (ZEEI). On the one hand, there are courts that explain that confinement in lieu of a fine is contrary to UNCLOS 1982, while on the other hand it is said that it does not violate UNCLOS 1982. This study was conducted to provide a legal study of whether the imposition of confinement in lieu of a fine on perpetrators of IUU Fishing in ZEEI. The results of this study, namely according to the interpretation of grammatical and the meaning of words/terms (taalkundige interpretation) and the explanation of legal experts, can be concluded that imprisonment and confinement (including confinement in lieu of a fine) are included in the scope of the prohibition of Article 73 paragraph (3) of UNCLOS 1982, because this punishment eliminates a person's freedom. Courts in Indonesia should be consistent not implementing imprisonment and corporal punishment considering that Indonesia has ratified UNCLOS 1982 and is bound by the principle of pacta sunt servanda. This paper provides proposals to amend the Fisheries Law and Judges are also encouraged to make independent legal discoveries to create substitute criminal sanctions for fines that do not conflict with UNCLOS 1982.